Chemical Strategies towards the Synthesis of Betulinic Acid and Its More Potent Antiprotozoal Analogues - Cunha, André Barreto (Molecules, 2021)
Betulinic acid (BA, 3β-hydroxy-lup-20(29)-en-28-oic acid) is a pentacyclic triterpene acid present predominantly in Betula ssp. (Betulaceae) and is also widely spread in many species belonging to different plant families. BA presents a wide spectrum of remarkable pharmacological properties, such as cytotoxic, anti-HIV, anti-inflammatory, antidiabetic and antimicrobial activities, including antiprotozoal effects. The present review first describes the sources of BA and discusses the chemical strategies to produce this molecule starting from betulin, its natural precursor. Next, the antiprotozoal properties of BA are briefly discussed and the chemical strategies for the synthesis of analogues displaying antiplasmodial, antileishmanial and antitrypanosomal activities are systematically presented. The antiplasmodial activity described for BA was moderate, nevertheless, some C-3 position acylated analogues showed an improvement of this activity and the hybrid models—with artesunic acid—showed the most interesting properties. Some analogues also presented more intense antileishmanial activities compared with BA, and, in addition to these, heterocycles fused to C-2/C-3 positions and amide derivatives were the most promising analogues. Regarding the antitrypanosomal activity, some interesting antitrypanosomal derivatives were prepared by amide formation at the C-28 carboxylic group of the lupane skeleton. Considering that BA can be produced either by isolation of different plant extracts or by chemical transformation of betulin, easily obtained from Betula ssp., it could be said that BA is a molecule of great interest as a starting material for the synthesis of novel antiprotozoal agents.